Perbandingan Penentuan Waktu Baku Menggunakan Metode Time Study dan Critical Path Method (CPM) - Suci Miranda; Wawan Tripiawan (Jurnal Sistem dan Manajemen Industri, 2019)
Increased technological developments encourage companies or industries to be able to increase their productivity. Increased productivity can do with improvements in each process carried out following the standard time set to complete an activity. This study aims to compare the usual time in the production process of MP YST Revo at a metal casting company using the time study method and the Critical Path Method (CPM) approach. Both methods process the same information for the duration of each recorded activity and allowance. The time study calculates the standard time of the production process by considering allowances, while the CPM uses completion time and final coefficient where the sum of the duration of each activity entering the critical path becomes completion time. Based on four observations, the average of the 30-minute allowance obtained, and the average observed time is 450.05 minutes, and the CPM gives a faster completion time of 341.4 minutes. The standard time to use CPM offers a difference of about 2 hours faster than a time study.